2006
DOI: 10.1016/j.idairyj.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined high pressure and enzymatic treatments on the hydrolysis and immunoreactivity of dairy whey proteins

Abstract: The effect of high-pressure (HP) treatment on the hydrolysis of dairy whey proteins by trypsin, chymotrypsin and pepsin was analysed. Isostatic pressure (100-300 MPa for 15 min at 37 1C) was applied to the protein substrate prior to its enzymatic hydrolysis. Digestion was also conducted at atmospheric pressure (0.1 MPa) and under high pressure. The extent of hydrolysis was measured by the o-phthaldialdehyde method, the peptide profile was analysed by reverse-phase high performance liquid chromatography (RP-HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 16 publications
4
46
0
3
Order By: Relevance
“…HHP treatment favours the activity of trypsin on the Hb molecule because pressurized samples showed higher intensity of hydrolysis than control ones. These results were in agreement with Peñas et al (2004;2006a), who reported an increase in hydrolysis by trypsin and chymotrypsin for bovine whey and soybean whey proteins treated by high pressure before or during the hydrolysis reaction, as a result of denaturation of the proteins induced by HHP and dissociation into monomers. According to these authors, the increase in proteolysis when HHP was applied during the hydrolysis could be related to protein denaturation allowing the exposure of the susceptible peptide bonds to the active protease.…”
Section: Non-protein Nitrogen (Nnp)supporting
confidence: 92%
See 1 more Smart Citation
“…HHP treatment favours the activity of trypsin on the Hb molecule because pressurized samples showed higher intensity of hydrolysis than control ones. These results were in agreement with Peñas et al (2004;2006a), who reported an increase in hydrolysis by trypsin and chymotrypsin for bovine whey and soybean whey proteins treated by high pressure before or during the hydrolysis reaction, as a result of denaturation of the proteins induced by HHP and dissociation into monomers. According to these authors, the increase in proteolysis when HHP was applied during the hydrolysis could be related to protein denaturation allowing the exposure of the susceptible peptide bonds to the active protease.…”
Section: Non-protein Nitrogen (Nnp)supporting
confidence: 92%
“…Quirós et al (2007) proposed a method for the commercial production of bioactive peptides from ovalbumin, consisting on HHP treatment of egg white proteins followed by hydrolysis with proteases. Moreover, according to Peñas et al (2004;2006a;2006b), increased yields of hydrolysates from bovine whey and soybean proteins can also be obtained when combining enzymatic and HHP treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The major whey proteins are b-lactoglobulin (BLG, 55-60%) and a-lactalbumin (ALA,(15)(16)(17)(18)(19)(20); other minor proteins are bovine serum albumin, immunoglobulins, lactoferrin and phospholipoproteins (Peñas, Préstamo, Baeza, Martínez-Molero, & Gomez, 2006). BLG is absent in human milk and may induce allergies in infants because of the underdevelopment of their gastrointestinal tract and immune system (Pintado, Pintado, & Malcata, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Peñ as, Pré stamo, Baeza,Martínez-Molero, & Gó mez, 2006;Peñ as et al, 2006b;Peñ as, Snel, Floris, Pré stamo, & Gó mez, 2006) and soybean WP(Peñ as et al, 2004(Peñ as et al, , 2006aPeñ as, Pré stamo, Polo, & Gó mez, 2006) performed under high pressure. The unfolded proteins formed under MWI could represent an ideal substrate for the action of proteases, making some epitopes more accessible to enzymatic hydrolysis.4.…”
mentioning
confidence: 99%